Episodes of Early Pleistocene West Antarctic Ice Sheet Retreat Recorded by Iceberg Alley Sediments. Issue 7 (12th July 2022) - Bailey, Ian; Hemming, Sidney; Reilly, Brendan T.; Rollinson, Gavyn; Williams, Trevor; Weber, Michael E.; Raymo, Maureen E.; Peck, Victoria L.; Ronge, Thomas A.; Brachfeld, Stefanie; O'Connell, Suzanne; Tauxe, Lisa; et al.
Abstract: Ice loss in the Southern Hemisphere has been greatest over the past 30 years in West Antarctica. The high sensitivity of this region to climate change has motivated geologists to examine marine sedimentary records for evidence of past episodes of West Antarctic Ice Sheet (WAIS) instability. Sediments accumulating in the Scotia Sea are useful to examine for this purpose because they receive iceberg‐rafted debris (IBRD) sourced from the Pacific‐ and Atlantic‐facing sectors of West Antarctica. Here we report on the sedimentology and provenance of the oldest of three cm‐scale coarse‐grained layers recovered from this sea at International Ocean Discovery Program Site U1538. These layers are preserved in opal‐rich sediments deposited ∼1.2 Ma during a relatively warm regional climate. Our microCT‐based analysis of the layer's in‐situ fabric confirms its ice‐rafted origin. We further infer that it is the product of an intense but short‐lived episode of IBRD deposition. Based on the petrography of its sand fraction and the Phanerozoic 40 Ar/ 39 Ar ages of hornblende and mica it contains, we conclude that the IBRD it contains was likely sourced from the Weddell Sea and/or Amundsen Sea embayment(s) of West Antarctica. We attribute the high concentrations of IBRD in these layers to "dirty" icebergs calved from the WAIS following its retreat inland from its modern grounding line. These layers also sit at the top of a ∼366‐m thick Pliocene and early Pleistocene sequence that is much more dropstone‐rich than its overlying sediments. We speculate this fact may reflect that WAIS mass‐balance was highly dynamic during the ∼41‐kyr (inter)glacial world. Plain Language Summary: If the West Antarctic Ice Sheet melted completely it would raise global sea‐level by ∼4.3 m and displace hundreds of millions of people currently living below high‐tide lines. This concern has motivated scientists to examine Antarctic‐proximal marine sediments for evidence of elevated iceberg‐rafted debris (IBRD) deposition indicative of ice‐sheet instability during the warmer than present geological past. Marine archives recovered recently by deep‐sea drilling of the Scotia Sea (aka. Iceberg Alley) by the International Ocean Discovery Program are ideal to examine for this purpose because many icebergs calved from Antarctica (and the IBRD they contain) end up here. To date, nothing is known, however, about IBRD deposition in Iceberg Alley prior to the Last Glacial Maximum nor its regional source(s). We show that three IBRD layers indicative of intense centennial‐paced episodes of iceberg calving to Iceberg Alley ∼1.2 million years ago were likely sourced from West Antarctica. These layers sit at the top of a ∼366‐m sequence that is more IBRD‐rich than its overlying sediments. We speculate that these observations reflect that West Antarctic Ice Sheet retreat was more frequent during the early Pleistocene than the last 1.2 million years. Key Points: We present the first provenance data generated for Pleistocene‐aged iceberg‐rafted debris deposited in Iceberg Alley We conclude that prominent iceberg‐rafted debris layers deposited at Pirie Basin Site U1538 ∼1.2 Ma were sourced from West Antarctica They represent intense suborbitally‐paced episodes of iceberg discharge from tidewater glaciers, most likely in the Weddell Embayment